2014
DOI: 10.1080/19463014.2014.888360
|View full text |Cite
|
Sign up to set email alerts
|

Locating agency in the classroom: A metaphor analysis of teacher talk in a college developmental reading class

Abstract: This study employed a metaphor analysis approach to investigate instructor language as it relates to the positioning of agency within a college developmental reading course context. Agency, or the socioculturally mediated potential to act, is a crucial part of self-regulated, self-efficacious learning and contributes to identity formation and affirmation. Understanding where agency is being positioned via classroom discourse can have important implications for the teaching and learning transaction, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Focusing on metaphors, the present study addressed one aspect of individual understanding of academic reading. In contrast to earlier studies (Paulson & Armstrong, 2011;Paulson & Theado, 2015; for studies on other academic practices see Saban, Kocbeker & Saban, 2007;Wegner & Nückles, 2015a, 2015b, we identified a large variety of conceptual metaphors. Although we could cluster them into a few discernable groups, there is considerable intra-group variability, especially if one takes transitivity, that is, the amount of agency and impact, into account.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Focusing on metaphors, the present study addressed one aspect of individual understanding of academic reading. In contrast to earlier studies (Paulson & Armstrong, 2011;Paulson & Theado, 2015; for studies on other academic practices see Saban, Kocbeker & Saban, 2007;Wegner & Nückles, 2015a, 2015b, we identified a large variety of conceptual metaphors. Although we could cluster them into a few discernable groups, there is considerable intra-group variability, especially if one takes transitivity, that is, the amount of agency and impact, into account.…”
Section: Discussionmentioning
confidence: 57%
“…As mentioned above, metaphor use and recognition are important cognitive strategies because they allow to understand new or abstract concepts in terms of interactions with the physical world or bodily states, for instance as taking things up or immersing oneself into a book. Many studies analyzed those metaphors in terms of a few, often only two or three, underlying broad categories (Paulson & Armstrong, 2011;Paulson & Theado, 2015;Saban, Kocbeker & Saban, 2007;Wegner & Nückles, 2015a, 2015b) -such as learning as uptake of pre-existing ideas, learning as problem solving and learning as development of personality (Wegner & Nückles, 2016). However, people use many more metaphors than just these, and this variety is not only across persons (and groups such as different student groups or different disciplines and cultures), but may also arise within persons, for instance when talking to different others or in different situations or faced with different tasks.…”
Section: Approach To Metaphorsmentioning
confidence: 99%
“…Following the methods of Paulson and Theado [11] we closely examined the participants' responses by breaking them down into individual metaphorical expressions. The metaphorical expressions were identified using source domain elements to describe features of the target domain.…”
Section: Discussionmentioning
confidence: 99%
“…While the first answer sounds quite normative (it is just to confirm CMT's idea of how a metaphor occurs naturally in daily communication), the second seems to go with a number of findings revealing positive contributions of metaphorical teacher talks towards the learning process in the EFL classroom. Thu (2019) found that teacher's metaphorical instructions help students improve their writing skills, and previously, Paulson and Theado (2015) discovered that teacher's metaphorical talks can make new and unfamiliar concepts more meaningful to students. The findings seem to imply that a metaphorical talk can be an effective tool that a teacher can use to facilitate skill and knowledge acquisition process in the classroom.…”
Section: Metaphorical Teacher Talkmentioning
confidence: 95%
“…From here, it can simply be learnt that the EFL classroom does need metaphors, both as concepts or cognitive processes and linguistic expressions. In fact, as claimed by Paulson and Theado (2015), metaphors can make new and unfamiliar concepts more meaningful to learners; analogical reasoning through metaphors enhances students' motivation and knowledge acquisition; and students' critical thinking skill can become better through metaphors.…”
Section: Introductionmentioning
confidence: 98%